Multiple cycle frequencies estimation under cochannel interference - Yang, John Xingguang (2020)
In this letter, two cycle frequencies estimation algorithms are proposed to estimate the number of weak cyclostationary signals and their cycle frequencies in the presence of higher power interferer signal. Both cycle frequencies estimation algorithms are eigenanalysis-based methods that use the cyclic autocorrelation function of the received signals. In particular, a new eigen-analysis cyclic null spectrum is introduced to determine the number of cyclostationary signals and estimate their cycle frequencies. The performances of the proposed cycle frequency estimation algorithms are demonstrated with numerical examples and compared with the existing cycle frequency estimation algorithms. It is shown that both the proposed cycle frequencies estimation algorithms have better accuracy than the existing methods and could work with small sample size for faster estimation.